764 Paediatric Emergency Appendicectomy in a District General Hospital: A Review of Current Practice. (19th August 2022) - Armstrong, L; Ali, T
Abstract: Aim: Appendicitis is one of the most common surgical pathologies amongst children, with approximately 80% in the UK admitted and managed in district general hospitals. The Royal college of Surgeons paediatric emergency appendicectomy commissioning guidelines state a negative appendicectomy rate should be <15% and <1% should be admitted following a prior discharge with no intervention. We aimed to review current practice and adherence to guidelines. Method: A retrospective review was carried out of all paediatric patients admitted with suspected appendicitis, in a single centre over a 1-year period. Demographics, pre-operative investigations, technique, histology, length of stay, readmissions, complications, and transfers to tertiary centres were recorded. Results: Total of 101 patients admitted within audit window with a median age of 9.5 years, 50.5% male. Average length of stay was 2 days. Total of 30 appendicectomies performed (63.3% laparoscopic). Negative appendicectomy rate 23.3% (n=7). Seventeen underwent a pre-operative ultrasound, 2 of which confirmed appendicitis and proceeded to an appendicectomy. The remaining 15 were successfully discharged. 28-day readmission rate returned at 5.94%. 1 (0.99%) patient was readmitted following a prior discharge with no intervention and subsequently underwent an appendicectomy, revealing acute appendicitis. No patients were transferred to a tertiary centre. Conclusions: Overall, favourable comparison to published guidelines, however higher than optimal negative appendicectomy rate. Utilisation of preoperative ultrasound may aid towards the reduction of this figure. Guideline also states patients should be taken to theatre within 12 hours of decision to operate. Further review of patient's notes should be performed to determine this.